منهج القران وإعجازه الموسيقى في الايات الكونية؛ دراسة تحليلية خلال فنّ الطبا في جزء عمّ - Wan Azura Wan Ahmad; Ahmad Sanusi Azmi; Adnan Yusof; Hisyamuddin Ahmad; Rabiatul Adawiyah Muhamad; Zaini Zakaria; Zati Adlin Mat Jalil (Centre of Quranic Research (CQR), University of Malaya, 2024)
Antithesis (al-Tibaq) is one of the semantic embellishment which is found variously in the Quran, Sunnah, and always used among the rhetorical scholars. It is one of the greatest enhancers effect in the beautification of the style; highlighting the meanings, because it transcends the phenomena of words to the intonation, and does not stand at the words itself, but exceed the meanings. The significance of this study in its attempt to highlight the hidden significance and the secret of the miracle of Qur'anic interpretation, and then detect the aesthetics style of the Holy Quran rhetorically especially acoustical terms in it. Furthermore, it is important to highlight the importance of using proper pronunciation and word of emphasis meaning and integration between word and meaning in the Quran. And all this come out through a deep analysis of the Quranic evidence reveals three aspects, namely: the purpose of rhetoric, rhetorical semantics, as well as the mystery of miracles in the Holy Quran. The study concluded that the hidden connotations of the al-Tibaq, especially in the kawniyyat verses (related to the creation), played a major role in highlighting the Quranic rhetoric and its aesthetics in the Qur'anic verses, as well as its role in highlighting the acoustical miraculous of the Holy Quran.